2014
DOI: 10.5935/0034-7167.20140053
|View full text |Cite
|
Sign up to set email alerts
|

Embracement and anxiety symptoms in patients before cardiac surgery

Abstract: RESUMOTrata-se de ensaio clínico randomizado, em que se objetivou comparar a frequência e intensidade de sintomas de ansiedade de pacientes em pré-operatório de cirurgia cardíaca que receberam acolhimento do enfermeiro ou do familiar ou os que não receberam nenhum tipo específico de acolhimento. A amostra foi constituída de 66 pacientes em pré-operatório de cirurgia cardíaca, que foram alocados em três grupos: acolhimento pelo enfermeiro, sem acolhimento específico e acolhimento pelo familiar. A ansiedade foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
(23 reference statements)
2
7
0
10
Order By: Relevance
“…This study showed that patients who leaned on religious coping strategies and social support also had better results after the surgery (17) . A national study showed that the consideration provided by the presence of the family is more significant for coping than the contact of nurses only, which was evaluated by lower levels of anxiety (18) . Using other evaluation tools, a national study showed improvement in quality of life regarding the generic aspects of mental health and emotional aspects after heart surgery, even without considering the spiritual and religious aspect (19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that patients who leaned on religious coping strategies and social support also had better results after the surgery (17) . A national study showed that the consideration provided by the presence of the family is more significant for coping than the contact of nurses only, which was evaluated by lower levels of anxiety (18) . Using other evaluation tools, a national study showed improvement in quality of life regarding the generic aspects of mental health and emotional aspects after heart surgery, even without considering the spiritual and religious aspect (19) .…”
Section: Discussionmentioning
confidence: 99%
“…This instrument is a protocol of free use worldwide used both in research and in clinics to assess the levels of anxiety of patients undergoing a surgical experience. It consists of 21 items, with response alternatives ranging from nothing to mild, moderate, and severe, about which each subject reflects on the gradational levels of each symptom, being anxiety rated in minimal (0-10), mild (11)(12)(13)(14)(15)(16)(17)(18)(19), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and severe (31-63) (9) .…”
Section: Study Protocolmentioning
confidence: 99%
“…Ainda, estudos trazem como perfil de pacientes submetidos à CRM a baixa escolaridade, com no máximo primeiro grau completo, ou cerca de cinco anos de estudo (9,(11)(12) , e em condição de aposentadoria (11) , normalmente com ocupações anteriores que geravam rendas de até três salários mínimos ou donas de casa, no caso de mulheres (9) . Ao analisar o tempo de chegada do paciente com infarto agudo do miocárdio na emergência, estudo revelou que, mesmo com uma população com poucos anos de estudo, o reconhecimento dos sinais e dos sintomas de IAM foi fator determinante para a procura de atendimento especializado em tempo hábil (13) .…”
Section: Discussionunclassified
“…No Brasil, estudos realizados com pacientes submetidos a CRM mostram que mais de 50% dos participantes apresentaram patologias pré-existentes, sendo as de maior distribuição a HAS e o DM (12,(17)(18) . Estudos similares mostraram que mais da metade dos participantes com insuficiência coronariana submetidos a CRM apresentam fatores de risco para DCV, sendo a pressão arterial elevada a mais prevalente, seguido da dislipidemia, DM, tabagismo (9,(19)(20) e história familiar para DCV (17,20) .…”
Section: Discussionunclassified
“…In addition, both the patient and his/her family member (or accompanying person) present anxiety before the procedure. (3)(4)(5)(6) Both feelings can cause physiologic changes in the patient, such as increased heart rate and blood pressure, which increase the consumption of oxygen and thereby worsen the development of the disease. In addition, these symptoms occur during invasive procedure, such as cardiac catheterization, and they can increase the duration of and may cause difficulties during the procedure, as well as leading to possible changes in the results of the exam and physical harm to the patient.…”
Section: Introductionmentioning
confidence: 99%